TCR-engaging scaffolds selectively expand antigen-specific T-cells with a favorable phenotype for adoptive cell therapy - Marco Donia; Özcan Met; Julie Westerlin Kjeldsen; Sine Reker Hadrup; Inge Marie Svane; Arianna Draghi; Anders Handrup Kverneland; Christina Heeke; Siri Amanda Tvingsholm; Marcus Svensson Frej; Vibeke Mindahl Rafa; Ulla Kring Hansen; et al. (Journal for ImmunoTherapy of Cancer)
Background Adoptive cell therapy (ACT) has shown promising results for the treatment of cancer and viral infections. Successful ACT relies on ex vivo expansion of large numbers of desired T-cells with strong cytotoxic capacity and in vivo persistence, which constitutes the greatest challenge to current ACT strategies. Here, in this study, we present a novel technology for ex vivo expansion of antigen-specific T-cells; artificial antigen-presenting scaffolds (Ag-scaffolds) consisting of a dextran-polysaccharide backbone, decorated with combinations of peptide-Major Histocompatibility Complex (pMHC), cytokines and co-stimulatory molecules, enabling coordinated stimulation of antigen-specific T-cells.Methods The capacity of Ag-scaffolds to expand antigen-specific T-cells was explored in ex vivo cultures with peripheral blood mononuclear cells from healthy donors and patients with metastatic melanoma. The resulting T-cell products were assessed for phenotypic and functional characteristics.Results We identified an optimal Ag-scaffold for expansion of T-cells for ACT, carrying pMHC and interleukin-2 (IL-2) and IL-21, with which we efficiently expanded both virus-specific and tumor-specific CD8+ T cells from peripheral blood of healthy donors and patients, respectively. The resulting T-cell products were characterized by a high frequency of antigen-specific cells with high self-renewal capacity, low exhaustion, a multifunctional cytokine profile upon antigen-challenge and superior tumor killing capacity. This demonstrates that the coordinated stimuli provided by an optimized stoichiometry of TCR engaging (pMHC) and stimulatory (cytokine) moieties is essential to obtain desired T-cell characteristics. To generate an ‘off-the-shelf’ multitargeting Ag-scaffold product of relevance to patients with metastatic melanoma, we identified the 30 most frequently recognized shared HLA-A0201-restricted melanoma epitopes in a cohort of 87 patients. By combining these in an Ag-scaffold product, we were able to expand tumor-specific T-cells from 60–70% of patients with melanoma, yielding a multitargeted T-cell product with up to 25% specific and phenotypically and functionally improved T cells.Conclusions Taken together, the Ag-scaffold represents a promising new technology for selective expansion of antigen-specific CD8+ T cells directly from blood, yielding a highly specific and functionally enhanced T-cell product for ACT.